ANALYSIS OF OWN ERRORS OF THE FIRST 100 LAPAROSCOPIC GASTRIC BANDING - M. Е. Margolin; E. I. Margolina (Креативная хирургия и онкология, 2017)
Article is devoted to the analysis of own material on performance of laparoscopic gastric banding for the purpose of treatment of morbidny obesity. Authors considered most often meeting difficulties performing the  operation and  frustration arising in the  postoperative period  and  complications. On the  basis of the  saved-up experience the  thesis  about need of technical ensuring operation and thorough preparation of the medical personnel and the patient is given.